Tiga Jenis Kecerdasan dan Agresivitas Mahasiswa - Rahmat Aziz; Retno Mangestuti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
This research aimed to find out the relation between three kinds of intelligences (intellectual, emotional, and spiritual intelligence) and aggression. The proposed hypothesis is that there is a negative correlation between three kinds of intelligences and level of aggression in college students. Population of this reasearch are student of Islamic State University of Malang from varied discipline such as Faculty of Tarbiyah, Faculty of Humaniora, Faculty of Science and Technology, Faculty of Psychology, Faculty of Economic and Faculty of Syariah. Subject were 304 students. Data were collected using Aggression Scale, Emotional Intelligence Scale, Spiritual Intelligence Scale, and SPM (Standard Progressive Matrices) as an instrument to measure intellectual intelligence. Data analyzed by regression analysis technique. The more intelligence student, the less aggressive he/she is. The research also find that the three kind of intelligences have 32,5% portion on aggression.Keywords: intellectual intelligence, emotional intelligence, spiritual intelligence, aggression